Analisis Deiksis Dialek Kulisusu Masyarakat Desa Rante Gola Kecamatan Bonegunu Kabupaten Buton Utara - Stofiana, Tofan (Pustaka : Jurnal Ilmu-Ilmu Budaya, 2021)
This study aims to find out whether the sort card media can improve speaking skills in learning to tell the experience of students of class X-3 of SMAN 2 Lasalimu Selatan. This research was compiled based on the Classroom Action Research (CAR) design which was divided into two cycles with four stages per cycle, namely planning, action, observation and reflection. The first cycle was held from 9 to 14 January 2017. The second cycle was held on January 16 to 21 2017 in class X-2 of SMAN 2 Lasalimu Selatan. The results of the study show that the use of sort card media increases speaking skills in learning to tell the experience of X-3 grade students of SMAN 2 Lasalimu Selatan. This increase is indicated by the acquisition of success percentage of 67.44% in the first cycle and increased by 5.36% in the second cycle to reach the success percentage of 76.33%